Myasthenia gravis and Lambert-Eaton myasthenic syndrome: treatment options and guidance for management during COVID-19 pandemic - Klimašauskienė , A.; Bunevičiūtė , R. (Neurologijos seminarai, 2020)
Myasthenia gravis (MG) and Lambert-Eaton myasthenic syndrome (LEMS) are immune-mediated neurologic disorders characterized by muscle weakness and fatigue. MG is the most common neuromuscular junction disorder while LEMS is an extraordinary rare disease. The symptomatic treatment of MG and LEMS includes acetylcholinesterase inhibitors. Amifampridine (3,4-diaminopyridine) is effective in reducing symptoms of the LEMS. Long term immunosuppressive treatment involves corticosteroids, azathioprine, and mycophenolate mofetil. Thymectomy is an essential component of treatment for thymomatous MG patients. Thymectomy also has a therapeutic role for selected non-thymomatous MG patients. The treatment of severe exacerbations and myasthenic crises includes intravenous immunoglobulins and plasma exchange. During the COVID-19 pandemic, MG/LEMS patients should continue ongoing treatment and are advised not to stop any immunosuppressive agents used. Altering or stopping an immunosuppressive agent may increase disease activity and/or MG exacerbation or crisis. Immune depleting agents should not be given if symptoms and signs of serious infections appear.